Monotowns in Russia and in other Countries: Similiarities and Differences - SATYBALDINA, Elena Vladimirovna (Journal of Advanced Research in Law and Economics; Vol 6 No 2 (2015): JARLE Volume VI Issue 2(12) Summer 2015, 2016)
The situation in mill towns or monotowns (calque from Russian monogorod) in modern economy is particular sharp that cause the necessity to research modern Russian mill towns and to reveal social problems of the towns of such type. The author analyses main characteristics of city-forming enterprise because its effective operation determines all dimensions of life and social welfare of monoprofile town. Comparison with company towns of the USA, including Pullman and Menlo Park was chosen by the author as effective method of diagnostics of Russian mill town state. Author reviews G. Pullman's conception of company town that has been laid in the foundation of modern company towns of the new generation. Comparison allows revealing the range of problems and advantages and disadvantages of this phenomenon. Main characteristics of living in Ural mill town and Facebook company town are being compared. Influence of monotown specifics are analyzed together with the history of foundation that have strong effect on everybody in these towns and have high potential of further development. Possible ways of relieving tension in such towns are proposed.
Keywords: monoprofile town, company town, company town conception, city-forming enterprise